Prolonged Sojourn at Very High Altitude Decreases Sea-Level Anaerobic Performance, Anaerobic Threshold, and Fat Mass - Szymczak, Robert K.; Grzywacz, Tomasz; Ziemann, Ewa; Sawicka, Magdalena; Laskowski, Radosław (Frontiers in Physiology, 2021)
(1) Background: The influence of high altitude on an organism’s physiology depends on the length and the level of hypoxic exposure it experiences. This study aimed to determine the effect of a prolonged sojourn at very high altitudes (above 3500 m) on subsequent sea-level physical performance, body weight, body composition, and hematological parameters. (2) Material and Methods: Ten alpinists, nine males and one female, with a mean age of 27 ± 4 years, participated in the study. All had been on mountaineering expeditions to 7000 m peaks, where they spent 30 ± 1 days above 3500 m with their average sojourn at 4900 ± 60 m. Their aerobic and anaerobic performance, body weight, body composition and hematological parameters were examined at an altitude of 100 m within seven days before the expeditions and seven days after they descended below 3500 m. (3) Results: We found a significant (p < 0.01) decrease in maximal anaerobic power from 9.9±1.3 to 9.2±1.3 W·kg-1, total anaerobic work from 248.1±23.8 to 228.1±20.1 J·kg-1, anaerobic threshold from 39.3±8.0 to 27.8±5.6 mlO2·kg-1·min-1, body fat mass from 14.0±3.1 to 11,5±3.3 %, and a significant increase (p < 0.05) in maximal tidal volume from 3.2 [3.0—3.2] to 3.5 [3.3—3.9] L after their sojourn at very high attitude. We found no significant changes in maximal aerobic power, maximal oxygen uptake, body weight, fat-free mass, total body water, hemoglobin and hematocrit. (4) Conclusions: A month-long exposure to very high altitude led to impaired sea-level anaerobic performance and anaerobic threshold, increased maximal tidal volume, and depleted body fat mass, but had no effect on maximal aerobic power, maximal oxygen uptake, or hemoglobin and hematocrit levels.